PENERAPAN MODEL PEMBELAJARAN INKUIRI UNTUK MENINGKATKAN HASIL BELAJAR IPA KELAS IVb SD NEGERI 168 PEKANBARU - ', Aguslina; ', Syahrilfuddin; Marhadi, Hendri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The problem this research is the students achievement of social fourth graderes studies still low with an average value of 63,04 and minimum completeness criteria (KKM) social studies is 70. Between students, amounting to 28 people only 12 students who achieve classical KKM with 42,85%. This research is Classroom Action Research (CAR), which aims to improve the student achievement of science studies class IVb at SDN 168 Pekanbaru with implementation  model problem inkuiri. Formulation of the problem : Is the implementation  of problem inkuiri can improve students achievement of social studies at SDN 168 Pekanbaru. The research was conducted month April. Subjects were students of SDN 168Pekanbaru, totaling 28 people who use the data source. The data collection instruments in this thesis is a teacher and students activities sheets and students achievement. This thesis presents the results obtained each day before the action  an improve in base score cycle with the average being 63,04. In the first cycle improve an average of 70,97 with increase big as 73,65. Activities of the teacher in the learning process in cycle of 1with increase big as and the second meeting improve to 60% and the second meeting improve 65%. Cycle II first meeting and the second meeting improve 70% to 80%. In the third cycle of the first meeting and the second meeting improve 95% to 55% and the second meeting impove 65%. Results of data analysis of students activities in the first cycle with the first meeting of an average of 70% and a second meeting improve to 75% in the class IVb at SDN 168 Pekanbaru that the implementation of problem inkuiri can improve the student achievement of science studiesat fourth graderes SDN 168 Pekanbaru.                     Key Words: Model Problem Inkuiri, fourth graderes Students Science.